Role of insulin-like growth factor 1 on cross-bred Bos indicus cattle germinal vesicle oocytes exposed to heat shock - Lima, Rafaela S. [UNESP]; Risolia, Pedro H. B. [UNESP]; Ispada, Jéssica; Assumpção, Mayra E. O. A.; Visintin, José A.; Orlandi, Cássia; Paula-Lopes, Fabíola F. [UNESP] (CSIRO Publishing, 2017)
Germinal vesicle (GV) oocytes are susceptible to heat stress. However, neither the cellular mechanisms triggered by elevated temperature nor the thermoprotective effects of insulin-like growth factor (IGF) on GV oocytes are completely understood. Therefore, a series of experiments was conducted to determine the direct effects of IGF1 (0, 12.5, 25, 50 and 100ng mL-1) on heat-treated GV oocytes. Butyrolactone-arrested GV oocytes were cultured at 38.5°C (control) or 41°C (heat shock; HS) for 14h in the presence of different concentrations of IGF1. Exposure of GV oocytes to 41°C increased (P<0.05) the number of terminal deoxyribonucleotidyl transferase-mediated fluorescein-dUTP nick end-labelling (TUNEL)-positive oocytes. At concentrations of 12.5 and 25ng mL-1, IGF1 tended to minimise these negative effect of HS (P≤0.07). However, neither HS nor IGF1 had any effect on caspase activity. HS also decreased (P<0.05) GV oocyte mitochondrial activity and developmental competence to the blastocyst stage. These deleterious effects of HS were alleviated (P<0.05) by 12.5ng mL-1 IGF1. This concentration of IGF1 did not affect cleavage rate, the percentage of TUNEL-positive blastomeres and total blastocyst cell number regardless of temperature. In conclusion, exposure of GV oocytes to HS triggered the apoptotic cascade and compromised oocyte developmental competence. Physiological concentrations of IGF1 had a beneficial effect on heat-shocked GV oocytes.
Keywords: apoptosis; development; growth factor; IVF.